¡Pertenecemos y tenemos importancia aquí! Exploring Sense of Belonging and Mattering for First-Generation and Continuing-Generation Latinx Undergraduates. Issue 1 (February 2020) - Dueñas, Mary; Gloria, Alberta M.
Using a psychosociocultural approach, we examined the role of motivation, belonging, and congruity relative to sense of mattering for 236 Latinx undergraduates attending a public Midwest research university. Findings revealed the key role of belonging in understanding undergraduates' experiences where belonging accounted for more than half of the variance of mattering as well as mediated the relationship of congruity and mattering. Differences by college generation, academic certificate, and student organization status were also revealed. Practical implications for faculty, administrators, and university personnel and future direction for research are addressed relative to student affiliation and sense of belonging and mattering.